A Descriptive Analysis of Young Learnersâ Behaviours toward TEFL - Anwar, Choiril; Kusumawarni, Wa Ode runi (State Institute of Islamic Studies Salatiga, 2018)
This research was surely aimed at investigating young learnersâ behaviors toward the teaching English as a foreign language (TEFL). This qualitative research used descriptive method. It was conducted in SD Islam Sultan Agung 4 Semarang. The population of this research was the students of grade 5 and students of grade 6 in the academic year of 2017/2018 with the total sample was 70 students, consisting of 32 students of Grade VA and 38 students of Grade VI. In this research, the researchers used convenience sampling to determine the sample of the research. The variables of this study were teaching English as a foreign language which is as independent variable and young learnersâ behavior functions as dependent variable. The data collection techniques of this research were through 1) observation and 2) close-ended questionnaire. The results of the research then indicated that young learners showed positive behaviors toward the teaching English as a foreign language such as paid attention to the teacherâs explanation, wrote down and read the material, actively and bravely in asking questions to the teacher, and made the vocabularies list to be memorized.Keywords:Â Teaching English as a Foreign Language; Behavior; Young Learners